Skilful decadal-scale prediction of fish habitat and distribution shifts - Mark R. Payne; Gokhan Danabasoglu; Noel Keenlyside; Daniela Matei; Anna K. Miesner; Shuting Yang; Stephen G. Yeager (Nature Communications, 2022)
Advances in climate prediction mean that the state of the ocean and the drivers of shifts can be skilfully forecast up to a decade ahead. This study applies decadal-scale climate predictions to forecast shifts in the habitat and distribution of marine fish species, providing information relevant to stakeholders and a tool to foresee and adapt to the challenges of a changing climate.